Analisis Brand Experience Dan Brand Commitment Terhadap Brand Loyalty (Study Pada Konsumen Go-Jek Yang Berada Di Dinoyo) - Rofikul A’la; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research to analyze Brand Experience and Brand Commitment on Brand Loyalty with go-jek for the the study case in Dinoyo city, the variable used is Brand Loyalty for independent variable with Brand Experience and Brand Commitment for dependent variable, this research study type is explanatory research with quantitative approach which used questionnaire for instuments research and distributed to respondents which amounts to 96 people for sampel. Data in this research processing with SPSS 20 application for windows, The result of study in partially that conclude there are had influence between Brand Experience and Brand Commitment on Brand Loyalty with positive and significant, that result from regresion test, Brand experience and Brand Commitment on Brand Loyalty had signification score more than 0,05 and in simulanerous Brand Experience and Brand Commitment had influence effect on Brand Loyalty together that from result of regresion test that had signification score more than 0,05 and Fvalue 31,019. Keyword : Brand Experience,Brand Commitment,Brand Loyalty